Functional Activation of Osteoclast Commitment in Chronic Lymphocytic Leukaemia: a Possible Role for RANK/RANKL Pathway. Issue 1 (December 2017) - Marini, Cecilia; Bruno, Silvia; Fiz, Francesco; Campi, Cristina; Piva, Roberta; Cutrona, Giovanna; Matis, Serena; Nieri, Alberto; Miglino, Maurizio; Ibatici, Adalberto; Maria Orengo, Anna; Maria Massone, Anna; et al.
Abstract Skeletal erosion has been found to represent an independent prognostic indicator in patients with advanced stages of chronic lymphocytic leukaemia (CLL). Whether this phenomenon also occurs in early CLL phases and its underlying mechanisms have yet to be fully elucidated. In this study, we prospectively enrolled 36 consecutive treatment-naïve patients to analyse skeletal structure and bone marrow distribution using a computational approach to PET/CT images. This evaluation was combined with the analysis of RANK/RANKL loop activation in the leukemic clone, given recent reports on its role in CLL progression. Bone erosion was particularly evident in long bone shafts, progressively increased from Binet stage A to Binet stage C, and was correlated with both local expansion of metabolically active bone marrow documented by FDG uptake and with the number of RANKL + cells present in the circulating blood. In immune-deficient NOD/Shi-scid, γcnull (NSG) mice, administration of CLL cells caused an appreciable compact bone erosion that was prevented by Denosumab. CLL cell proliferationin vitro correlated with RANK expression and was impaired by Denosumab-mediated disruption of the RANK/RANKL loop. This study suggests an interaction between CLL cells and stromal elements able to simultaneously impair bone structure and increase proliferating potential of leukemic clone.